Literature Review ESG and Sustainability Finance - Dina Hastalona; Isfenti Sadalia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Nowadays, the corporate performance is not only measured by financial ratio, the company’s contribution to environmental sustainability, the welfare of the surrounding community is currently part of the corporate’ performance. It can be said to be successful if it consider economic, environmental and social aspect. This literature review describes several studies related to socially responsible investment. The result show that the application of CSR or ESG practices has an effect on the sustainability of the company’s business, and many researchers measure it by firm value. There is also a contradiction between the influence of ESG on the sustainability of the corporate’s business, and it turns out that what affects it is the time frame. The application of CSR practices ESG disclosure have a positive effect on the long term business performance and not the short term’s corporate performance.